2021
DOI: 10.3389/fpsyg.2021.699088
|View full text |Cite
|
Sign up to set email alerts
|

Pre-retirement Employees Experience Lasting Improvements in Resilience and Well-Being After Mindfulness-Based Stress Reduction

Abstract: The socio-economic benefits of interventions to prevent stress and related mental health problems are enormous. In the labor market, it is becoming desirable to keep employees for as long as possible. Since aging implies additional stressors such as increased risk of illness, and added pressure by professional tasks such as transferring knowledge, or learning new technologies, it is of particular relevance to offer stress-reduction to pre-retirement employees. Here, we report the effects of an eight-week Mindf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
3
11
0
Order By: Relevance
“…The opponents of the p -value corrections approach contend that type I error is dissipated to overall hypotheses rather than being localized to one or several hypotheses ( Matsunaga, 2007 ; Rubin, 2017b ). While we acknowledge both views are valid, we followed the no-adjustment approach as well as the other social science studies ( Ding et al, 2020 ; Diachenko et al, 2021 ; Thériault et al, 2021 ) by conceding the potential problems of the taken approach.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The opponents of the p -value corrections approach contend that type I error is dissipated to overall hypotheses rather than being localized to one or several hypotheses ( Matsunaga, 2007 ; Rubin, 2017b ). While we acknowledge both views are valid, we followed the no-adjustment approach as well as the other social science studies ( Ding et al, 2020 ; Diachenko et al, 2021 ; Thériault et al, 2021 ) by conceding the potential problems of the taken approach.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Construct validation of BRS has not been performed in a Danish context. However, previous Danish research studies have shown the effect of MBSR on BRS ( Juul et al, 2020 ; Diachenko et al, 2021 ).…”
Section: Methodsmentioning
confidence: 85%
“…Previous trials had shown the effect of MBSR on resilience. These trials included study populations at an older age and with lower levels of baseline resilience scores although within the normal range ( Juul et al, 2020 ; Diachenko et al, 2021 ). It was also very unexpected that our trial did not show a statistically significant effect of the mindfulness program on dispositional mindfulness and thereby no mediating effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations